Modifikasi Sistem Kontrol Heater Dengan Display Thermocontrol dan Sensor Thermocouple Pada Mesin Cutting Wind Up ITL.01.TL.01 - Wahyu Pebriansyah Asmara; Paul Michael Siahaan; Dharmanto; Choirunnisa, Anis; Aliifah, Naila Zulfa (Jurnal Instrumentasi dan Teknologi Informasi (JITI), 2025)
PT. XYZ, a motorcycle tire factory, encountered a malfunction in the ITL.01.TL.01 cutting machine due to an overheating heating system. This research aims to modify the heating system on the ITL.01.TL.01 machine used for cutting inner liners. Manual cutting caused variations in inner liner length (73-78 meters), impacting production efficiency and consistency. The improvement method involved modifying the heater control system. Data were obtained through direct observation and analyzed using descriptive statistics. The modification, including the addition of a thermocouple sensor for real-time temperature monitoring, improved accuracy and efficiency in temperature control. Power calculations showed that the modified system operated with better energy efficiency. Paired T-test analysis indicated a significant performance improvement after the modification. These modifications allowed the cutting machine to operate, reducing material length variation and increasing overallefficiency.